Implementasi Pembelajaran Holistik dalam Pendidikan Anak Usia Dini: Tantangan Guru dan Strategi Pengembangan Anak - Sakiratul Niam; Rahma Anisa; Dian Anggraini; Nadia Rizqiah; Novita Loka (CV. Jalan Cendikia, 2026)
Holistic learning is an important approach in early childhood education that integrates all aspects of children's development comprehensively. This study aims to explore and analyze the challenges faced by teachers and the strategies developed in implementing holistic learning at TK Negeri Pembina Tanjung Batu. The study employed a descriptive qualitative approach with research subjects including 19 children from Group B Mecca (aged 5-6 years), 3 classroom teachers, and the principal. Data collection techniques used participatory observation, in-depth interviews, and documentation. Data analysis using the Miles and Huberman model included data reduction, data presentation, and conclusion drawing. The results showed that the main challenges faced by teachers include managing children's emotions who bring bad moods from home (5.3%) and handling hyperactive children (15.8%). The strategies developed by teachers include personal approaches to identify the causes of problems, intensive communication with children and parents, modification of learning activities according to individual needs, and involving parents and the surrounding environment as learning partners. Children's developmental achievements showed 42.1% in the Very Well Developed (BSB) category, 36.8% Developed As Expected (BSH), 15.8% Starting to Develop (MB), and 5.3% Not Yet Developed (BB). The implementation of holistic learning at TK Negeri Pembina Tanjung Batu demonstrates good integration between developmental aspects through meaningful activities with active parental involvement and utilization of the surrounding environment as learning resources.